Model referencyjny procesu logistyki zaopatrzenia - Jezierski, Andrzej (Referential Model of the Logistics Services Process, 2009)
The paper presents problems of managing the logistics services process. The paper focuses on the logistics service structures, especially the purchasing process. The author of the paper focuses on types of logistics management tools, barriers and limits that may interrupt the logistics process. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 281-286